2021
DOI: 10.1186/s12879-021-06815-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, subtypes and risk factors of Blastocystis spp. infection among pre- and perimenopausal women

Abstract: Background Blastocystis spp. are considered pathogenic or commensal organisms, although the majority of researchers suggest that these are neglected pathogens. The main aim of this study was to determine the prevalence and subtype distribution of Blastocystis spp. in pre- and perimenopausal women, with respect to socio-demographic (age and place of residence), and epidemiological factors, as well as drinking tap water, contact with domestic animals, traveling abroad, health status, and presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…It is suggested that ST3 is the most human-specific subtype and is primarily transmitted among people (due to human-to-human transmission) [ 63 ]. In Poland, ST3 is the most prevalent subtype in both, males and females, in various age groups as well as in those traveling outside Europe and the patients who never left their country [ 2 , 3 ]. Regarding ST7 it is considered an avian subtype because of its higher frequency in animals, including livestock, and its relative predominance in birds, both wild and farmed [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that ST3 is the most human-specific subtype and is primarily transmitted among people (due to human-to-human transmission) [ 63 ]. In Poland, ST3 is the most prevalent subtype in both, males and females, in various age groups as well as in those traveling outside Europe and the patients who never left their country [ 2 , 3 ]. Regarding ST7 it is considered an avian subtype because of its higher frequency in animals, including livestock, and its relative predominance in birds, both wild and farmed [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Positive PCR products were purified using Clean-Up (A&A Biotechnology, Poland) according to the manufacturer’s recommendations. The entire procedure of DNA extraction from feces, the PCR method was described previously by Kosik-Bogacka et al [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, Blastocystis was predominantly characterized as a parasitic protozoa [ 53 ], but conflicting results regarding its pathogenic potential and clinical significance have emerged in several studies [ 40 ]. Blastocystis has been associated with the etiology of irritable bowel syndrome (IBS) [ 54 , 55 , 56 , 57 ] and IBD [ 58 ]. In contrast, other cohort studies have found no correlation between gastrointestinal symptoms and the presence of Blastocystis, either in healthy subjects or IBS patients [ 59 , 60 ].…”
Section: Intestinal Protozoa—pathogenic Commensal or Beneficial?mentioning
confidence: 99%
“…The most prevalent subtypes in Polish people are 1-3 and 7, with a low (6-10%) prevalence. European people are generally infected by Blastocystis subtypes 1-4 [17,18]. In Polish chickens, subtypes 5-7 were noted [19].…”
Section: Introductionmentioning
confidence: 99%